Beyond the 'teachable moment' – A conceptual analysis of women's perinatal behaviour change. Issue 3 (June 2016) - Olander, Ellinor K.; Darwin, Zoe J.; Atkinson, Lou; Smith, Debbie M.; Gardner, Benjamin
Abstract: Background: Midwives are increasingly expected to promote healthy behaviour to women and pregnancy is often regarded as a 'teachable moment' for health behaviour change. This view focuses on motivational aspects, when a richer analysis of behaviour change may be achieved by viewing the perinatal period through the lens of the Capability–Opportunity–Motivation Behaviour framework. This framework proposes that behaviour has three necessary determinants: capability, opportunity, and motivation. Aim: To outline a broader analysis of perinatal behaviour change than is afforded by the existing conceptualisation of the 'teachable moment' by using the Capability–Opportunity–Motivation Behaviour framework. Findings: Research suggests that the perinatal period can be viewed as a time in which capability, opportunity or motivation naturally change such that unhealthy behaviours are disrupted, and healthy behaviours may be adopted. Moving away from a sole focus on motivation, an analysis utilising the Capability–Opportunity–Motivation Behaviour framework suggests that changes in capability and opportunity may also offer opportune points for intervention, and that lack of capability or opportunity may act as barriers to behaviour change that might be expected based solely on changes in motivation. Moreover, the period spanning pregnancy and the postpartum could be seen as a series of opportune intervention moments, that is, personally meaningful episodes initiated by changes in capability, opportunity or motivation. Discussion: This analysis offers new avenues for research and practice, including identifying discrete events that may trigger shifts in capability, opportunity or motivation, and whether and how interventions might promote initiation and maintenance of perinatal health behaviours.